Deconvoluting Charge Transfer Mechanisms in Conducting Redox Polymer-Based Photobioelectrocatalytic Systems. Issue 8 (1st August 2022) - Weliwatte, N. Samali; Simoska, Olja; Powell, Daniel; Koh, Miharu; Grattieri, Matteo; Whittaker-Brooks, Luisa; Korzeniewski, Carol; Minteer, Shelley D.
Abstract : Poor electrochemical communication between biocatalysts and electrodes is a ubiquitous limitation to bioelectrocatalysis efficiency. An extensive library of polymers has been developed to modify biocatalyst-electrode interfaces to alleviate this limitation. As such, conducting redox polymers (CRPs) are a versatile tool with high structural and functional tunability. While charge transport in CRPs is well characterized, the understanding of charge transport mechanisms facilitated by CRPs within decisively complex photobioelectrocatalytic systems remains very limited. This study is a comprehensive analysis that dissects the complex kinetics of photobioelectrodes into fundamental blocks based on rational assumptions, providing a mechanistic overview of charge transfer during photobioelectrocatalysis. We quantitatively compare two biohybrids of metal-free unbranched CRP (polydihydroxy aniline) and photobiocatalyst (intact chloroplasts), formed utilizing two deposition strategies ( "mixed" and "layered" depositions). The superior photobioelectrocatalytic performance of the " layered" biohybrid compared to the " mixed" counterpart is justified in terms of rate ( D app ), thermodynamic and kinetic barriers (H ≠, E a ), frequency of molecular collisions ( D 0 ) during electron transport across depositions, and rate and resistance to heterogeneous electron transfer ( k 0, R CT ). Our results indicate that the primary electron transfer mechanism across the biohybrids, constituting the unbranched CRP, is thermally activated intra- and inter-molecular electron hopping, as opposed to a non-thermally activated polaron transfer model typical for branched CRP- or conducting polymer (CP)-containing biohybrids in literature. This work underscores the significance of subtle interplay between CRP structure and deposition strategy in tuning the polymer-catalyst interfaces, and the branched/unbranched structural classification of CRPs in the bioelectrocatalysis context.